Association of Macrolide Resistance Genotypes and Synergistic Antibiotic Combinations for Combating Macrolide-Resistant MRSA Recovered from Hospitalized Patients - Bishr, Amr S. (Biology (Basel), 2021)
SIMPLE SUMMARY: Macrolide-resistant methicillin-resistant Staphylococcus aureus (MAC-MRSA) is one of the most clinically relevant pathogens due to its significant ability of resistance acquisition to different antimicrobial agents and narrow therapeutic options. This study aimed to evaluate antimicrobial susceptibility and the use of different combinations of azithromycin with other antibiotics as well as studying the correlation of MAC resistance genotypes and antimicrobial agents that provided synergy when they were combined with azithromycin. Azithromycin (AZM) combinations with either linezolid, ceftriaxone, gentamicin, or cefotaxime provided synergy in 42.1%, 44.7%, 31.6% and 7.9% of the 38 MAC-MRSA isolates, respectively. Statistical analysis showed significant association between the presence of the ermA genotype and the synergism of AZM + ceftriaxone and AZM + gentamicin; the presence of the ermC genotype and the synergism between AZM and gentamicin; the presence of the msrA genotype and the synergism between AZM and ceftriaxone; and the presence of the ermA/msrA genotype and the synergism between AZM and cefotaxime. The obtained findings will guide clinicians in better choosing the antibiotic combinations required for combating MAC-MRSA clinical isolates. However, the promising synergistic antibiotic combinations must be re-evaluated in vivo using an appropriate animal model. ABSTRACT: Macrolide-resistant methicillin-resistant Staphylococcus aureus (MAC-MRSA) is one of the most clinically relevant pathogens due to its significant ability of resistance acquisition to different antimicrobial agents. This study aimed to evaluate antimicrobial susceptibility and the use of different combinations of azithromycin with other antibiotics for combating MAC resistance. Seventy-two Staphylococci (38.5%) (n = 187), showed resistance to MACs; of these, 53 isolates (73.6%, n = 72) were S. aureus and 19 (26.4%, n = 72) were coagulase-negative staphylococci (CoNS). Out of the 53 S. aureus and 19 CoNS isolates, 38 (71.7%, n = 53) and 9 (47.4%, n = 19) were MRSA and methicillin-resistant CoNS, respectively. The constitutive MACs, lincosamides and streptogramin-B (cMLS) comprised the predominant phenotype among S. aureus isolates (54.7%) and CoNS isolates (78.9%). The PCR analysis showed that the ermC gene was the most prevalent (79.2%), followed by msrA (48.6%), and ermA (31.9%). Azithromycin combinations with either linezolid, ceftriaxone, gentamicin, or cefotaxime provided synergy in 42.1%, 44.7%, 31.6% and 7.9% of the 38 MAC-MRSA isolates, respectively. Statistical analysis showed significant association between certain MAC resistance genotypes and the synergistic effect of certain azithromycin combinations (p value < 0.05). In conclusion, azithromycin combinations with either linezolid, or ceftriaxone showed synergism in most of the MAC-resistant MRSA clinical isolates.